Effect of Kersen Leaf Flour (Muntingia Calabura L.) Fermented in the ration against the growth of super free-range chickens aged 3-10 weeks - Agustinus Budigo; I Nyoman Kaca; Ni Made Yudiastari (GEMA AGRO, 2025)
Indonesia's livestock sector is currently developing very quickly due to public awareness of the nutritional value of animals, one of which is from super free-range chickens. Super free-range chickens or superior broiler chickens are the result of a cross between free-range chickens and egg-laying breed chickens. The purpose of the study was to find out the effect of giving fermented Japanese papaya leaf flour on the growth of super free-range chickens aged 3 - 10 weeks. Super free-range chickens in their maintenance need quality feed to fulfill their nutrition. However, rations are the largest cost component, which is 60-80% of the total production cost of poultry, so there needs to be an effort to reduce the conversion value by using other feed alternatives, but without reducing the productivity of the livestock. Kersen leaves contain nutrients that also have anti-bacterial properties and contain phytochemicals including flavonoids, tannins, triterpenes, and saponins that show antioxidant activity The nutritional content of kersen leaf flour is 5.02% water, 6.39% ash, 11.31% crude protein, 14.85% crude fiber, 7.53% fat, 69.75% carbohydrates and 3988 kcal/kg of metabolic energy. Kersen leaves can be used as feed ingredients in rations by fermenting to reduce the crude fiber (14.85%) it contains. The design used in this study is a Complete Random Design (RAL) with 5 treatments and 3 replicates. P0 = A ration without containing fermented kersen leaf flour. P1 = The ration contains 3% fermented kersen leaf flour. P2= The ration contains 6% fermented kersen leaf flour. P3 = The ration contains 9% fermented Japanese kersen leaf flour. P4 = The ration contains 12% fermented kersen leaf flour. The indicators observed were initial body weight, weight gain, final body weight, ration consumption and Feed Conversion Ratio (FCR). The results of the study showed that the growth of super free-range chickens fed a ration of fermented kersen leaf flour showed different results (P>0.05) on initial body weight, weight gain, final body weight and FCR, while in ration consumption there was a real effect (P<0.05). Based on the results of this study, in the P1 treatment, the administration of fermented cool leaf flour gave the best results by giving 3%.